Does the Expansion of Farmers’ Operation Scale Improve the Efficiency of Agricultural Production in China? Implications for Environmental Sustainability - Zhang, Qing; Razzaq, Amar; Qin, Jun; Feng, Zhongchao; Ye, Feng; Xiao, Meizhen (Frontiers in Environmental Science, 2022)
China’s agricultural development urgently needs dynamic transformation and green transformation, from a traditional extensive mode of production to a moderately intensive mode of production that meets the requirements of the new era, with efficiency improvement as the guide to promote green, low-carbon, and sustainable development. Based on the micro-data of farmers in Hunan province from 2015 to 2020, this paper uses the data envelopment analysis method to measure the cost efficiency of rapeseed production and then decompose the cost-efficiency. The Tobit model is used to analyze the influencing factors and cost-efficiency differentials. First, there is considerable room for improvement in the overall cost efficiency of Chinese rapeseed production. The technical efficiency (TE), allocation efficiency (AE), and cost efficiency (CE) of rapeseed production in the survey area are 0.869, 0.701, and 0.609, respectively. Second, allocative efficiency is an important factor affecting the improvement of cost efficiency. The expansion of farmers’ operation scales does not necessarily improve their allocative efficiency, but increases their input of chemical fertilizer and other elements, which may lead to agricultural non-point source pollution. This is not conducive to sustainable environmental development. Third, the relationship between the cost efficiency of crop production and farmers’ operation scale is of an “inverted U-type” curve. That is to say, with the expansion of farmer operation scale, cost-efficiency shows an “increasing first and decreasing later” trend peaking at (6.67,13.33) hm2. Fourthly, the distinguishing factors which affect cost efficiency show obvious similarities while reserving differences. Finally, we also suggest countermeasures and suggestions from the perspective of R & D investment, industrial support, regional exchange and cooperation, reasonable input of resource factors, and awareness of agricultural green production to promote green and low-carbon development of the rapeseed industry in China.